Exploring the Insecticide and Acaricide Potential of Development Regulators obtained from Restinga vegetation from Brazil - FEDER,DENISE (2019)
Abstract: As a part of our continuing search for insect and arthropod development regulators from Brazilian restinga vegetation of the Rio de Janeiro State, crude extracts, purified fractions and essential oils were submitted to screening tests seeking for biological activities on the development of the insects Rhodnius prolixus, Dysdercus peruvianus, Oncopeltus fasciatus and Rhipicephalus (Boophilus) microplus. Up to now, 102 secondary metabolites have been detected in the fractions, among them monoterpenes, sesquiterpenes and two triterpenes which were obtained from the species, Eugenia sulcata, Pilocarpus spicatus, Manilkara subsericea, Myrciaria floribunda and Zanthoxylum caribaeum. These secondary plant metabolites are considered of interest for the use of studies related to arthropod endocrinology, vector-parasite interaction system, and population control of vector insect and agricultural pest. The observed biological activities were surprisingly high, involving increased mortality, molting and metamorphosis inhibition, paralysis, corporeal deformities, apparition of permanent nymphs, of adultoids and juvenoids, partial or total inhibition of oviposition and egg hatching. These compounds are now being studied further to determine if they may or may not be useful in controlling insect populations and/or interfere with the life cycle and vector transmission of parasites to animal and human populations.